Blogging as a Tool for Real-Time Learning in Medical Microbiology - Lloyd, Charmaine (Frontiers in Microbiology, 2021)
Blogging is a widely used social medium for storing and sharing information online. Being an attractive online interface, some studies show that education blogging or edublogging might promote more engaged learning. An apathy to contemporary issues related to one’s area of study can result in a less knowledgeable student who is less ready for the job industry. To bridge the gap between classroom learning and awareness of emerging issues pertaining to the field of study and potential employment – blogging of ongoing events in a select microbiological field was proposed as a graded semester-long activity called “Disease Tracking.” The exercise involved instructing students to choose one infectious disease topic, for which traditional and non-traditional scientific information could be sourced with high frequency over the preceding months. Students were to document new information on the topic as it became available over the term, from reliable information resources. At the end of the term, students presented their work in a “Blog show-off” presentation session. Blog-based learning was found to be an engaging tool that satisfied all criteria under Bloom’s taxonomy. Students developed a continued intrigue for the chosen topic and appreciated the diverse fields in which fundamentals of infectious diseases learned in class, could be applied within and outside academia. Students also valued this experience and feedback showed that the freedom to choose their own topic (77%), opportunity to learn more from other students’ blogs (77%), less stress as they were not competing on identical topics (73%), a “fun way” to learn (68%), and an opportunity to understand the importance of staying abreast with scientific news (64%) stood out as the chief positive points of the exercise to the students. In view of these benefits, blogs can be used for an immersive, broad learning experience in Microbiology and other fields in which there is likely to be a frequency of new information online.